Surgery and Rehabilitation Following Flexor Tendon Zone II Injury Of The Hand: A Literature Review - Lumintang, Loelita Marcelia; Nata’atmadja, Beta Subakti (Lingkar Studi Bedah Plastik Foundation, 2017)
Background : Flexor tendon injury of the hand is common and it used to end up with poor outcomes. It gives negative effects to patient’s daily life. Successful treatment for these cases is a challenge for surgeons. Before 1967, Injury in Zone II was called as “No Man’s Land”. Flexor tendon repair and rehabilitation have been substantially improved through advances in repair and rehabilitation. Method : We reviewed literatures from PubMed, MEDLINE, Cochrane and Google Scholar. It was researched using the terms flexor tendon zone II injury, flexor tendon zone II repair and flexor tendon zone II rehabilitation. Topics covered included anatomy, suture repair and material, and rehabilitation. Result : There is no significant difference of rupture rates and functional outcomes in the number of core suture. Braided polyester suture is the choice for core suture and monofilament for peripheral suture. There is no significant difference in rehabilitation using early passive motion or early active motion. The preference for post operative treatment is by using short splint without immobilization of the wrist. Discussion : Repair sutures techniques and suture materials have been improved as well as active mobilization rehabilitation protocols including a change of wrist position by modification of splints. Improvement in putting splint from a traditional dorsal blocking splint into splint that not immobilize the wrist. Despite all of these modifications, tendon ruptures have not been eliminated. The definitive answer remains elusive.